2014
DOI: 10.1142/s0218202514400077
|View full text |Cite
|
Sign up to set email alerts
|

Addressing integration error for polygonal finite elements through polynomial projections: A patch test connection

Abstract: Polygonal finite elements generally do not pass the patch test as a result of quadrature error in the evaluation of weak form integrals. In this work, we examine the consequences of lack of polynomial consistency and show that it can lead to a deterioration of convergence of the finite element solutions. We propose a general remedy, inspired by techniques in the recent literature of mimetic finite differences, for restoring consistency and thereby ensuring the satisfaction of the patch test and recovering opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 48 publications
3
74
0
Order By: Relevance
“…Regarding the numerical integration of the cut cells, the quadtree-refinement based on a decomposition of the polygonal cell into quadrilaterals is favored and is used if not specified otherwise. The preference of this method is based on the fact that in the wide body of literature it is reported that this approach provides more accurate results [8,34].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the numerical integration of the cut cells, the quadtree-refinement based on a decomposition of the polygonal cell into quadrilaterals is favored and is used if not specified otherwise. The preference of this method is based on the fact that in the wide body of literature it is reported that this approach provides more accurate results [8,34].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Since a standard hextension is performed this behavior is not caused by the geometry approximation error. Instead its source is the inexact numerical integration of the stiffness matrix K and the load vector F. Talischi et al found that all available quadrature schemes are inaccurate even on regular n-gons due to the non-polynomial nature of the basis functions and therefore proposed polynomial projections to circumvent this shortcoming [8,121]. A second reason for this behavior can be attributed to artificial stress singularities that are introduced due to the parabolic mapping.…”
Section: Comparison Of Poly-fcm Results With P-fem Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we briefly discuss aspects of implementation of the proposed formulation. We begin by discussing the issue of numerical quadrature, which is nontrivial for polygonal finite elements (see, for example, [38,30,40]), and proceed to provide explicit expressions for the basis functions for the local spaces V k (E) and their polynomial corrections.…”
Section: Discretization Scheme Based On the Correctionsmentioning
confidence: 99%
“…We refer to the recent papers and monographs [19,8,17,9,13,15,28,30,31,33,35,34,36,39,40,24,32,21] as a brief representative sample of the increasing list of technologies that make use of polygonal/polyhedral meshes. We mention here in particular the polygonal finite elements, that generalize finite elements to polygons/polyhedrons by making use of generalized non-polynomial shape functions, and the mimetic discretisation schemes, that combine ideas from the finite difference and finite element methods.…”
Section: Introductionmentioning
confidence: 99%